Karakteristik Kekerasan Lasan Titik Gesekan dan Pengadukan pada Paduan Aluminium 5052-H112 - Armansyah; Juri Saedon; Ferdyanto; Nely Toding Bunga; James Julian (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa & Inovasi, 2022)
Issues in friction stir spot welding focus mainly on the mechanical characteristic affected by its Hardness. This Hardness must be maintained by evenly temperature distribution in weld zones during welding. The process parameters are mainly responsible for the development of the hardness of the friction stir spot weld. This study presented the hardness evaluations on the friction stir spot weld via the Hardness-Vickers test and analysis of the temperature distribution in the weld zones via the finite element method. The workpiece samples used in this study were Aluminium alloy 5052-H112 with a thickness of 2 millimeters in the lap-shear mode based on 3 main parameters at low and high levels of parameters configuration. The results obtained via the Hardness-Vickers tests exhibited a value of 42-HV located in the middle of the spot-weld center using a low-level parameters configuration. This value increased to 64-HV around the vicinity of the keyhole. And then the value decreased to 53-HV outside the keyhole, about 6 millimeters from the spot-weld center. Using high-level parameter configuration, the Hardness-Vickers value increased to 61-HV in the middle of the spot-weld center. The value then increased to 76-HV in the vicinity of the keyhole. Furthermore, the value decreased at 60-HV outside the keyhole, which ca 6 millimeters away from the spot-weld center. The temperature distribution of the weld zones achieved 480 oC in the vicinity of the keyhole using the low-level parameter configuration. Slowly, the temperature declined to 380 oC at 6 mm away from the friction spot-weld center in the HAZ. Using the high-level parameters configuration, the temperature distribution reached 540 oC in SZ, and slowly reduced to 425 oC in HAZ. Based on the results, it was found that by using high-level parameters configuration the hardness of the friction stirs spot weld exhibited better Hardness-Vickers value and evenly temperature distribution in the weld zones.